Observational multicentre prospective study to assess changes in cognitive function in patients treated with PCSK9i. Study protocol - José Seijas-Amigo; Diego Rodríguez-Penas; Ana Estany-Gestal; Pedro Suárez-Artime; María Santamaría-Cadavid; José Ramón González-Juanatey (Elsevier, 2021)
Objective: PCSK9 inhibitors have been shown to reduce LDLc by up to about 60% and 85% when used with high doses of statins and ezetimibe (2019 ESC/EAS Guidelines). These therapies may lead to very low levels of LDLc and have been associated with possible cognitive deterioration. No significant differences were found in the only specific study (EBBINGHAUS). The objective is to prospectively evaluate cognitive deterioration and its repercussion on quality of life and changes in LDLc in patients starting treatment with PCKS9 inhibitors. Method: It is a postauthorization, multicentre, non-randomized, prospective study. Patients starting treatment for the first time with PCSK9 inhibitors will be recruited in 11 Galician Hospitals over a period of 12 months and with 24 months of follow-up. The primary outcome will be to evaluate changes in cognitive function using the Montreal Cognitive Assessment (MOCA) questionnaire. The secondary outcome will be to evaluate changes in quality of life using the EuroQol-5D. Changes in LDLc will be assessed. The sample size will be 275 patients, taking into account a loss to follow-up of no more than 10%. The primary outcome will be studied through the dichotomous variable cognitive deterioration (0/1). Cognitive changes over the follow-up period will be analysed using the McNemar test. In addition, an analytical approach using logistic regression will be followed to identify patients at risk of cognitive deterioration. As a result, this analysis will obtain a frequency measurement: the odds ratio (OR). The specific objectives will be studied using bivariate analysis. Continuous contrast variables will be studied using the t-test or ANOVA and categorical variables will be studied using the chi- square test. Conclusions: The MEMOGAL study will provide information on safety in terms of cognitive deterioration in patients starting treatment with PCSK9 inhibitors.